2017
DOI: 10.1084/jem.20160927
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 cooperates with FLT3-ITD to induce leukemia

Abstract: Behrens et al. establish the interplay of activated FLT3 receptor and the phosphorylated RUNX1 transcription factor in uncoupling proliferation and differentiation signals in acute leukemia. These findings demonstrate that RUNX1 is a viable therapeutic target in FLT3-mutated AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 75 publications
(99 reference statements)
4
29
0
Order By: Relevance
“…Moreover, a recent study has identified that HHEX is particularly highly expressed in AML with FLT3-internal tandem duplication (ITD). 43 This study also found that HHEX is a transcriptional target of RUNX1 in FLT3-ITD-associated AML and cooperates with FLT3-ITD to induce myeloid leukemia in vivo. These data validate our finding that Hhex overexpression cooperates with growth factor signaling to elicit myeloid leukemia, and suggest that this process also occurs in certain subsets of human AML.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, a recent study has identified that HHEX is particularly highly expressed in AML with FLT3-internal tandem duplication (ITD). 43 This study also found that HHEX is a transcriptional target of RUNX1 in FLT3-ITD-associated AML and cooperates with FLT3-ITD to induce myeloid leukemia in vivo. These data validate our finding that Hhex overexpression cooperates with growth factor signaling to elicit myeloid leukemia, and suggest that this process also occurs in certain subsets of human AML.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, we identified some common integration sites shown in Table 1 . Hhex (hematopoietically expressed homeobox) is a direct target of Runx1 and supports PRC2-mediated repression of Cdkn2a in AML cells ( Shields et al, 2016 ; Behrens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…The AML described here in detail carried mutations in Dnmt3a , Ezh2 , Runx1 , Nf1 , and Ep300 , all of which except for Ep300 caused deleterious changes in the sequences, confirmed by protein expression levels and activation of the MAPK pathway. Deletion of Dnmt3a , Ezh2 , and Runx1 blocks differentiation, while deletion of Nf1 activates the Ras-MAPK pathway (Behrens et al, 2017; Challen et al, 2011; Heckl et al, 2014; Tanaka et al, 2012; Xie et al, 2014a). The combinatorial effects of these mutations likely generated a LIC population defined as L-GMP, initially characterized in MLL-rearranged murine AML (Cozzio et al, 2003; Krivtsov et al, 2006; Somervaille and Cleary, 2006).…”
Section: Discussionmentioning
confidence: 99%